Re-emergence of Mycoplasma pneumoniae before and after COVID-19 pandemic in Germany - Frederike Waldeck; Tobias Siegfried Kramer; Sebastien Boutin; Jens Matten; Jan Kramer; Jan Rupp (BMC Infectious Diseases)
Abstract Background Mycoplasma pneumoniae (M. pneumoniae) is a common pathogen of community-acquired pneumonia (CAP). Epidemics occur every 3–7 years especially in pediatric patients. We collected data from a large laboratory network in Germany to define the epidemiological dynamics in the pre- and post-COVID-19 pandemic period. Methods In this retrospective cohort study we included all patients that obtained targeted or multiplex PCR for M. pneumoniae from nasopharyngeal swabs, sputum or bronchoalveolar fluids from 2015 to 2024. Demographic data (age, sex, place of residence, in- or outpatient status) were compared between M. pneumoniae positive and negative patients and co-infections with bacterial or viral pathogens analyzed. Results We screened 38,204 patients for M. pneumoniae. We identified 1448 cases (3.8%) of M. pneumoniae (48.8% females). Pediatric patients ≤ 18 years represented 75.7% of M. pneumoniae patients and 2.3% were ≥ 60 years. Incidence of M. pneumoniae increased in fourth quartile 2015 (16.2%), second quartile 2018 (14.8%) and fourth quartile 2023 (13.4%). No cases were detected during COVID-19 pandemic 2021. Young age (aOR 0.98 95%-CI 0.97–0.98), outpatient status (aOR 0.56 95%-CI 0.43–0.71) and year of testing (OR dependent on year of testing) were predictors of M. pneumoniae detection in multivariate analysis (p < 0.001). We observed a significant increase in outpatients with M. pneumoniae after COVID-19 pandemic (86.7 vs. 96.5%, p = < 0.001, aOR 0.25, 95% CI 0.15–0.4). Conclusions Empirical treatment of CAP patients often does not include coverage of M. pneumoniae. A more thorough implementation of available surveillance data into clinical routine, respective therapies could be adapted more quickly during epidemic outbreaks of M. pneumoniae infections.